Trace elements [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery, 2020)
A woman's cryptic dying words in a Venetian hospice lead Commissario Guido Brunetti and his colleague, Claudia Griffoni, to uncover a threat to the entire region.